Improved Sorghum Variety A Forgotten Gold in the Kenya Drylands - Chimoita, Evans (University of Nairobi, 2020)
Agricultural extension and technology transfer services play a vital role in disseminating research knowledge, skills and income-generating strategies among the farming communities in Kenya. However, there exists a disconnect between the amount of information and technologies developed in research centres and what is implemented by farmers. Further, improved technologies are not reaching farmers for utilization as a result of weak linkages between the government's extension providers, who are charged with the responsibility of ensuring that the technologies transfer to the farmers for utilization. Moreover, the effectiveness of the Government of Kenya's extension sector service provision has greatly declined during the last decade due to structural adjustment programmes (SAPs) and liberalization policies. The sector further faces constraints such as reduced and aged extension staff and low funding for operations and maintenance services, leading to weak information dissemination networks.
Keywords: Agriculture; Drylands